CREST, a Cas13‐Based, Rugged, Equitable, Scalable Testing (CREST) for SARS‐CoV‐2 Detection in Patient Samples. Issue 2 (23rd February 2022) - Aralis, Zach; Rauch, Jennifer N.; Audouard, Morgane; Valois, Eric; Lach, Ryan S.; Solley, Sabrina; Baxter, Naomi J.; Kosik, Kenneth S.; Wilson, Maxwell Z.; Acosta‐Alvear, Diego; Arias, Carolina
Abstract: The COVID‐19 pandemic has taken a devastating human toll worldwide. The development of impactful guidelines and measures for controlling the COVID‐19 pandemic requires continuous and widespread testing of suspected cases and their contacts through accurate, accessible, and reliable methods for SARS‐CoV‐2 detection. Here we describe a CRISPR‐Cas13‐based method for the detection of SARS‐CoV‐2. The assay is called CREST (Cas13‐based, rugged, equitable, scalable testing), and is specific, sensitive, and highly accessible. As such, CREST may provide a low‐cost and dependable alternative for SARS‐CoV‐2 surveillance. © 2022 Wiley Periodicals LLC. Basic Protocol : Cas13‐ased detection of SARS‐CoV‐2 genetic material using a real‐time PCR detection system Alternate Protocol : Cas13‐based detection of SARS‐CoV‐2 genetic material using a fluorescence viewer Support Protocol 1 : LwaCas13a purification Support Protocol 2 : In vitro transcription of synthetic targets